English Teaching Techniques Applied To Promote Students' Participation In The Classroom: A Case StudyAt Smp N 2 Ngemplak Boyolali - LISTYANA , YASINTA DIKA (2012)
This study is carried out to describe English teaching techniques applied to promote students' participation. The study is also intended to give some contribution for the betterment of teaching English. The data of this research are in the form of excerpts transcribed from the English teachers' attitude and interview students and English teachers. The writer takes three English teachers and students of SMP N 2 Ngemplak as the subject of this research. The writer uses descriptive qualitative especially the ethnography research in analyzing the data. In conducting this study there are at least six major stages have been done:the kinds of teaching techniques, the materials, the media, the teacher's role, student's role, and students' participation to the teaching techniques applied by English teachers. The result of the study shows that there are some techniques which promote students' participation such as: grouping, discussion, using electronic media, listen a song, picture describing, picture and word cues, give an issue, paper conversation, peer editing, reading aloud in group, answering question, and checking. Beside there are some techniques which promote students participation, the writer also finds some techniques which do not promote students' participation such as: pattern drill, imitate, recognition, translation, dictation, reading aloud by teacher, and reading aloud by student.